Kutubusittah dan Kutubutis’ah - Nur Helmi; Miranti Adelia Afda; Riswan Berutu; Juli Julaiha; Ardiansyah Ardiansyah (Jurnal Ilmiah Wahana Pendidikan, 2023)
The bookkeeping of hadiths at the time of the Prophet Muhammad was not carried out as was the writing of the Koran, this was done because it was feared that there would be mistakes so that the verses of the Koran were combined with the hadiths of the Prophet. In the middle of the third century of Hijriyah, the hadith scholars finally made the rules and conditions in determining the authentic or da'if hadith. Based on the hard work and sincerity of the hadith scholars at that time, hadith books were published which contained authentic hadiths and protected from fake hadiths known as the polausittah (six books) and also the polacutis'ah (the nine books). . The purpose of this study is to describe how the books contained in the polausittah and the polacutisáh are. The method used in this study is a qualitative approach, with the type of library research research carried out by reviewing and collecting several previous books and journals that are relevant to this research in order to obtain in-depth material and discussion that examines the poleusittah and kukutis'ah.